Urinary β-trace protein: A unique biomarker to screen early glomerular filtration rate impairment. Issue 49 (December 2016) - Donadio, Carlo; Bozzoli, Laura
Abstract : Abstract: The screening for chronic kidney disease (CKD) patients needs the measurement of serum markers like creatinine. Our previous results indicated that urinary excretion of β-trace protein (BTP), a low-molecular-weight protein (23–29 kDa), is increased in CKD patients from stage 2. The aim of this study was to assess the major determinants of urinary excretion of BTP and to evaluate its feasibility as noninvasive marker of glomerular filtration rate (GFR) impairment. We studied 355 CKD patients (198 males), aged 15 to 83 years, in stable clinical conditions, classified in the different stages of CKD on the basis of GFR (renal clearance of 99m Tc-diethylenetriamine penta-acetic acid). At the same time, we measured serum and urinary creatinine and BTP, and urinary albumin. Urinary excretion of BTP and albumin was expressed as mg/g urinary creatinine. Fractional clearance of BTP was calculated as the ratio of BTP clearance to creatinine clearance (%). Urinary excretion of BTP is mainly determined by its serum concentration and by the level of GFR, and to a lower extent by urinary albumin excretion. In fact, urinary BTP (U-BTP) and fractional clearance of BTP progressively and significantly increased along with the reduction of GFR and the concurrent rise in serum BTP (S-BTP). The relationship of U-BTP with GFR was very similar to that of S-BTP with GFR: U-BTP mirrors S-BTP. The accuracy of U-BTP to screen patients with GFR <90 mL/min/1.73 m 2 was good (area under the curve 0.833), its sensitivity was 76.9%, specificity 80%, and positive predictive value 84.9%. Sensitivity of U-BTP was quite similar to that of S-BTP and serum creatinine. The major determinants of urinary excretion of BTP are S-BTP and GFR. U-BTP may be a suitable noninvasive marker to screen the general population for detection of GFR <90 mL/min/1.73 m 2 . Abstract : Supplemental Digital Content is available in the text